Birodalmak, szövetségi rendszerek, avagy integrációk épültek Köztes-Európában 1914-2004 között? : történeti-politikai füldrajzi esszévázlat - Hajdú, Zoltán (Közép-Európai Közlemények, 2015)
History of Europe between 1914-2004 was very complicated from the points of views of territo-rial processes. In 1914 some historical empires ruled the territory of the East-Central Europe. After the First World War peace regulations East-Central Europe was divided for small „national states”, infact for small multinational states. During the first part of the Second World War Germany ruled nearly the whole Europe, at the end of the War East-Central Europe took part of the Soviet ruled area. After the end of Cold War countries of East-Central Europe turned to be members of NATO and European Union.